(untitled) (American Journal of Islam and Society, 2003)
The title Kalila wa Dimna first came to my attention long ago in my second year of Arabic language study. Ahmad Amin mentions Kalila wa Dimna in passing in his autobiography, Hayati (Cairo: 1952), an excerpt of which I read in Farhat Ziadeh’s Reader in Modern Literary Arabic. Over the years, I tried occasionally to read a bit of the original and found the classical Arabic intimidating. The task of reviewing Munther Younes’s retelling of these stories represented the opportunity to taste the stories’ flavor without the drudgery of dictionary look-up. Among other accomplishments, Younes simplifies the grammar and lexicon to the point where intermediate students of Arabic will understand what they read without excessive struggle. This review will touch upon the structure and substance of Kalila wa Dimna itself and Younes’ approach to retelling the stories and their utilization as an Arabic language teaching tool. In the West, most of us hear and then read Aesop’s Fables as children. These stories, which date back as far as 620 BCE, feature anthropomorphic animals who play out their dramas and conflicts in order to teach a moral. Kalila wa Dimna, attributed to the Indian author Bidpai and written in Sanskrit during the third century, does much the same, but also includes a smattering of human characters. As Younes tells us, the Sassanid King Khosro Anoushrawan sent his physician Burzuwayh to India to collect and translate Bidpai’s fables into Persian. In the process, Burzuwayh added stories by other authors. What had now become a book was then translated into Syriac in 570; 200 years later, Abdullah ibn al-Muqafac translated it into Arabic. Since its Arabization some 12 centuries ago, Kalila wa Dimna